Apelinergic system in the kidney: implications for diabetic kidney disease. Issue 23 (10th December 2018) - Müller, Tilman; Kalea, Anastasia Z.; Marquez, Alonso; Hsieh, Ivy; Haque, Syed; Ye, Minghao; Wysocki, Jan; Bader, Michael; Batlle, Daniel
Abstract: The bioactive peptides of the apelinergic system and its receptor APJ have been shown to play a protective role in experimental cardiovascular and diabetic kidney disease (DKD). Mechanisms of this renoprotective effect remain to be elucidated. In this study, we examined the localization of APJ within the normal kidney and its kidney expression in the db/db model of DKD. The effect of hyperglycemia and angiotensin II on APJ was examined in cultured podocytes. In the glomerulus, APJ colocalized with podocyte but not endothelial cell markers. In podocytes stimulated with Pyr 1 Apelin‐13, a change in the phosphorylation status of the signaling proteins, AKT, ERK, and p70S6K, was observed with an increase 15 min after stimulation. Apelin‐13 decreased activity of Caspase‐3 in podocytes after high glucose treatment reflecting an antiapoptotic effect of APJ stimulation. In podocytes, APJ mRNA was downregulated in high glucose, when compared to normal glucose conditions and exposure to angiotensin II led to a further significant decrease in APJ mRNA. APJ and preproapelin mRNA levels in kidneys from db/db mice were markedly decreased along with decreased tubular APJ protein by western blotting and immunostaining when compared to db/m controls. In conclusion, the apelinergic system is decreased in kidneys from db/db mice. Within the glomerulus, APJ is mainly localized in podocytes and in this cell type its activation by Apelin‐13 abolishes the proapoptotic effect of high glucose, suggesting a potential therapeutic role of apelin and emerging agonists with extended half‐life for therapy of DKD. Abstract : The apelinergic system is decreased in kidneys from diabetic mice. Within the glomerulus, APJ is mainly localized in podocytes and in this cell type its activation by Apelin‐13 abolishes the proapoptotic effect of high glucose, suggesting a potential therapeutic role of apelin and emerging agonists with extended half‐life for therapy of diabetic kidney disease.